Serum angiopoietin-2/angiopoietin-1 ratio is associated with cardiovascular and all-cause mortality in peritoneal dialysis patients: a prospective cohort study - Li, Han; Song, Qianhui; Su, Xinyu; Shen, Yiwei; Yan, Hao; Yu, Zanzhe; Li, Zhenyuan; Yuan, Jiangzi; Huang, Jiaying; Ni, Zhaohui; Gu, Leyi; Fang, Wei (Renal failure, 2024)
Our objective was to examine the factors associated with the serum angiopoietin-2/angiopoietin-1 (Angpt-2/Angpt-1) ratio in peritoneal dialysis (PD) patients and to investigate the association between Angpt-2/Angpt-1 ratio and cardiovascular and all-cause mortality. Patients on PD who were prevalent between January 2014 and April 2015 in the center of Renji Hospital were enrolled. At the time of enrollment, serum and dialysate samples were collected to detect biochemical parameters, serum angiopoietin-2 and angiopoietin-1 levels. Patients were dichotomized into two groups according to a median of Angpt-2/Angpt-1 ratio and followed up prospectively until the end of the study. A total of 325 patients were enrolled, including 168 males (51.7%) with a mean age of 56.9 ± 14.2 years and a median PD duration of 32.4 (9.8-55.9) months. Multiple linear regression showed pulse pressure (β = 0.206, < .001) and high-sensitivity C-reactive protein (hs-CRP) (β = 0.149, = .011) were positively correlated with serum Angpt-2/Angpt-1 ratio, while residual renal function (RRF) (β= -0.219, < .001) was negatively correlated with serum Angpt-2/Angpt-1 ratio. Multivariate Cox regression analysis showed the high serum Angpt-2/Angpt-1 ratio was an independent predictor of cardiovascular mortality (hazard ratio (HR)=2.467, 95% confidence interval (CI) 1.243-4.895, = .010) and all-cause mortality (HR = 1.486, 95%CI 1.038-2.127, = .031). In further subgroup analysis by gender, a significant association was shown in high Angpt-2/Angpt-1 ratio with all-cause mortality in male ( < .05), but not in female patients ( >.05). High Angpt-2/Angpt-1 ratio is an independent risk factor for cardiovascular and all-cause mortality in PD patients.